Fluoride content in bottled drinking waters, carbonated soft drinks and fruit juices in Davangere city, India - Thippeswamy H; Kumar Nanditha; Anand S; Prashant G; Chandu G (Wolters Kluwer Medknow Publications, 2010)
Background: The regular ingestion of fluoride lowers the prevalence of dental caries. The total daily intake of fluoride for optimal dental health should be 0.05-0.07 mg fluoride/kg body weight and to avoid the risk of dental fluorosis, the daily intake should not exceed a daily level of 0.10 mg fluoride/kg body weight. The main source of fluoride is from drinking water and other beverages. As in other countries, consumption of bottled water, juices and carbonated beverages has increased in our country. Objective: To analyze the fluoride content in bottled water, juices and carbonated soft drinks that were commonly available in Davangere city. Materials and Methods: Three samples of 10 commercially available brands of bottled drinking water, 12 fruit juices and 12 carbonated soft drinks were purchased. Bottled water and carbonated soft drinks were stored at a cold place until fluoride analysis was performed and a clear juice was prepared using different fruits without the addition of water. Then, the fluoride analysis was performed. Results: The mean and standard deviation of fluoride content of bottled water, fruit juices and carbonated soft drinks were measured, which were found to be 0.20 mg (±0.19) F/L, 0.29 mg (±0.06) F/L and 0.22 mg (±0.05) F/L, respectively. Conclusion: In viewing the results of the present study, it can be concluded that regulation of the optimal range of fluoride in bottled drinking water, carbonated soft drinks and fruit juices should be drawn for the Indian scenario.